Measurements of exposure sound level LAE generated by passing vehicles for different road surface types - RUDNO-RUDZIŃSKA, Barbara (Archives of Acoustics, 2007)
The influence of the road surface types on the noise emission level is a significant source of uncertainty of road noise maps drawn up using computational methods. In such methods the influence of the road surface type is taken into account through a correction to the noise emission level determined for the so-called reference surface. Depending on the kind of carriageway surface and its condition the road noise emission level may vary by several dB, which significantly affects the determined road noise propagation range. The paper presents the results of pass-by noise measurements for vehicles moving in the real city traffic. The investigations were carried out for 11 road with different pavements typical for city streets in Poland, including asphalt, asphalt concrete, stone mastic asphalt and cobblestones pavements. Also the results of comparative analyses of measurements and NMPB calculations for the investigated are be presented.